(untitled) (Research, Society and Development, 2019)
The aim of this article is to share the results of the Master dissertation around the representations of basic literacy and literacy from elementary teachers of Maria de Lourdes Castro School. This study approach is a qualitative case study methodology, the data were collected through interviews with five teachers of elementary school, Maria de Lourdes Castro School, they were selected due to accessibility of the researcher. The data collected were analyzed by the categories which had emerged in the theoretical reference of basic literacy and social literacy. As the result, it was realized that the teachers have almost the same idea of basic literacy and literacy; the literacy is very close to the conception of apprehension of the language code. So, it was verified that there is a need for a continuous education to deepen the knowledge about basic literacy and literacy, that conclusion is also supported by the answers of the interviewed teachers.